Current views on lupus in children. Issue 2 (25th March 2023) - Smith, Eve M.D.; Lythgoe, Hanna; Hedrich, Christian M.
Abstract : Purpose of review: This manuscript provides an update on clinical and pathophysiological features of juvenile-onset systemic lupus erythematosis (jSLE), challenges applying adult-derived classification criteria, and recent advances in treatment and care. Recent findings: Significant scientific advances have improved the understanding of genetic factors (both genetic causes and risk alleles) and associated phenotypic features. Panels of urine/blood biomarker candidates aid in diagnosing jSLE, monitoring disease activity and predicting treatment response. Available classification criteria have been extensively assessed, with differences in clinical and immunological phenotypes of patients across age groups and ethnicities affecting their performance in jSLE. Therapeutic options remain limited and are based on protocols for adult-onset SLE patients. International efforts to inform development of a treat-to-target (T2T) approach for jSLE have yielded cohort-level evidence that target attainment reduces the risk of severe flare and new damage, and treatment compliance. Summary: Recent studies have significantly improved our understanding of jSLE pathogenesis, highlighting important differences between jSLE and adult SLE, and providing the basis of biomarker development and target-directed individualized treatment and care. Future work focused on development of a T2T approach in jSLE is eagerly awaited.